Glucose and lipid lowering effects of Enhydra fluctuans extract in cadmium treated normal and type-2 diabetic model rats - Mohammad Nazmul Hasan; Farah Sabrin; Begum Rokeya; Md Shahinul Haque Khan; Mahtab Uddin Ahmed; Abel Matondo; Md Morsaline Billah; Salima Akter (BMC, 2019)
Abstract Background Recent epidemiological and experimental studies suggest that cadmium and diabetes-related hyperglycemia may act synergistically to worsen metabolic regulation. The present study aims to evaluate the potential effects of Enhydra fluctuans extract in diabetes and dyslipidemia in cadmium (CdCl2) induced- normal and type 2 diabetic model rats. Method Forty-eight Long-Evans rats were divided equally into the following six groups: Normal Control (N-C), Normal treated with CdCl2 (N-Cd), Normal treated with plant extract (N-P), Normal treated with both plant extract and CdCl2 (N-PCd), Diabetic treated with plant extract (DM-P) and Diabetic treated with both plant extract and CdCl2 (DM-PCd). Blood glucose and other biochemical parameters were estimated by the enzymatic colorimetric method. Histological analysis of liver and heart was done by the hematoxylin-eosin (H & E) method. Results Twenty-one days treatment of E. fluctuans extracts at a dose of 200 mg/kg significantly reduced blood glucose level in N-PCd and DM-PCd (p < 0.05), and DM-P (p < 0.01) group. The plant extract had no direct effects on total blood lipids but, it had beneficial effects on TG/HDL-C ratio in N-P and DM-PCd groups (p < 0.05). Cd induction significantly reduced body weight [(N-Cd, N-PCd, DM-PCd) (p < 0.01)], and induced liver [N-Cd (p < 0.05), N-PCd, p < 0.001] and renal impairment [N-Cd (p < 0.05)]. In bi-variate association, a significant positive correlation between serum glucose and SGPT (p < 0.05) as well as SGPT and TG/HDL ratio (p = 0.019) was found in DM-P and in the merged group. The histology of liver and heart showed severe damages including inflammation, nuclear pyknosis, loss of myocardial fibers, necrosis and fibrosis in the Cd treated groups compared to plant treated groups. Conclusion E. fluctuans seems to have potent antihyperglycemic effects in diabetes and Cd toxicity along with partial antidyslipidemic properties in euglycemic and diabetic rats. Our study suggests a novel oral antihyperglycemic agent in the present environmental context.